LONG-TERM RETENTION RATE OF CERTOLIZUMAB PEGOL IN PATIENTS WITH AXIAL SPONDYLOARTHRITIS: DATA FROM THE TURKBIO REGISTRY - Karataş, Ahmet; Pehlıvan, Yavuz; Akar, Servet; Şenel, Soner; Guler, Aslihan Avanoglu; Gündüz, Özgül Soysal; Onen, Fatos (My University, 2025)
Aim: Selecting the most effective treatment plan for a patient represents one of the most challenging issues in contemporary rheumatology. Clinicians must consider the long-term retention rate and the reasons for discontinuing candidate drugs.This study aimed to assess the drug survival of certolizumab pegol (CZP) in patients with axial spondyloarthritis (ax-SpA) and identify predictors for discontinuation. Material and Methods: Data on patient characteristics, demographics, diagnosis, disease duration, treatment, and outcomes have been collected from the Turkish Biological (TURKBIO) Registry since 2011. By December 2020, 410 ax-SpA patients, treated with CZP, were included. Assessment of disease activity parameters was conducted at baseline and at regular follow-up intervals throughout the study period. Additionally, drug retention rates were evaluated through Kaplan-Meier survival analysis over the observation period. Results: The analysis revealed that CZP demonstrates a high long-term retention rate in ax-SpA. At 36 months, the retention rate of CZP among patients with ax-SpA was 71.5%. During follow-up, 92 (22.4%) patients discontinued CZP treatment, with inefficacy being the main reason for discontinuation (58.7% of patients who discontinued therapy, n=54). Patients who discontinued CZP had significantly higher health assessment questionnaire, bath ankylosing spondylitis (AS) functional index, and bath AS disease activity index values compared to those who continued with CZP. They were relatively older, had longer symptom duration, and had a higher prevalence of uveitis. Compared to patients who continued with CZP, those who discontinued CZP were more frequently co-treated with non-steroidal anti-inflammatory drugs (NSAIDs) (68.5% vs. 53.1%), methotrexate (24.1% vs. 6.9%), sulfasalazine (38.9% vs. 12.6%), and leflunomide (5.6% vs. 0.6%). However, co-treatment with NSAIDs or conventional synthetic disease-modifying anti-rheumatic drugs did not increase the retention rate of CZP. Conclusion: Real-world data from the TURKBIO registry reveal that CZP exhibits a high long-term retention rate in patients diagnosed with ax-SpA.
Keywords: Axial spondyloarthritis; drug survival; biological therapy; certolizumab pegol; tumor necrosis inhibitors